The Effect of Taxes, Exchange Rates, Leverage, and Bonus Mechanisms on Transfer Pricing in Manufacturing Companies Listed on The IDX - Wenny Anggeresia Ginting; Bee Arlita Ade Putri Br. Sitorus; Cindy Lorenza; Sania Surga Mas (Publikasi Indonesia, 2021)
This research examines the impact of taxes, exchange rates, leverage, and bonus mechanism on transfer pricing. Tax is calculated by dividing deferred tax expenses taxable by profits. The exchange rate is calculated by dividing foreign exchange profit and loss by profit and loss before tax. Leverage is calculated by dividing total debt by total assets. Bonus Mechanism is calculated by multiplying net profit year t by net profit year t-1 by 100%. The population in this research included 54 manufacturing firms listed on the Indonesia Stock Exchange in 2017-2019, with 29 samples examined across three years. This study is quantitative since the data is numerical, and the data analysis technique is multiple linear regression. The exchange rate has a substantial impact on transfer pricing, according to the findings of this research. Based on the study, the Adjusted R Square value is 0.104, which indicates 10.4% of the independent factors, namely tax, exchange rate, leverage, and bonus mechanism, impact the dependent variable, transfer pricing. The remaining 89.6% is affected by another variable.